Novel opportunities for purchasing intention of organic foods: Identifying how health awareness, perceived health value, and the antecedents of the Technology Adoption Model (TAM) affect consumers' purchase intention - Sablu Khan (Agora International Journal of Economical Sciences (AIJES), 2025)
It is becoming more and more important to comprehend how customers purchase health friendly organic goods. The goal of the current study is to evaluate consumers' buying intentions regarding healthy products (or health friendly) shopping. This study also looks at how customer intentions to buy organic products are influenced by health awareness, perceived value of organic products, perceived usefulness, and attitude toward utilizing them. Moreover, the research expands upon Davis's (1989) Technology Adoption Model (TAM) by including exogenous factors such as perceived health value and environmental awareness. This study has been conducted through data collection via a Google form survey from 260 customers. With the collected data, structural equation modeling (SEM) and validity and reliability testing were carried out. The current study's findings demonstrate that attitudes toward utilizing organic products are positively and differently impacted by environmental awareness and perceived health value. The study also discovered that consumers' intentions to acquire organic food products are significantly influenced by their attitudes and perceptions of their utility. The current work has implications that benefit academicians, marketers, consumers, and policy makers.
Keywords: 330; Organic food products; Health awareness; Perceived health value; perceived usefulness; attitude